FISH CONSUMPTION PREFERENCES OF PEOPLE LIVING IN THREE DIFFERENT SOCIOECONOMIC REGIONS OF KAYSERİ, TURKEY (Third Sector Social Economic Review, 2018)
Fish is a food that is recommended to be consumed at least twice a week. But the amount of consumption is not at the desired level in our country, Turkey.  This study was conducted to determine the amount, frequency, consumption and purchasing preferences of fish consumed by adults at three different socioeconomic levels in Kayseri and to determine consumers’ knowledge about healthy nutrition and fish consumption. A descriptive, cross-sectional research study was conducted on 1000 adults living in three different socioeconomic regions in Kayseri province center.  Data were gathered by a questionnaire  prepared with the support from a literature review. The median weekly fish consumption per capita was 93 g (3–1000) in Kocasinan, 117 g (17–1000) in Talas and 117 g (16–600) in Melikgazi according to the socioeconomic regions. Fish were often consumed freshly and in winter. Only 21.6% of the participants consumed fish 1–2 times a week, as recommended. This rate increased, as the socioeconomic level increased. It is suggested that the accessibility of fish in Kayseri be increased and that studies should be carried out to raise awareness and educate people on the importance of fish consumption and its effects on health.
Keywords: Fish consumption; food preference; Kayseri; nutrition; socioeconomic level.